Data-driven evaluation of real estate liquidity : predicting days on market to optimize the sales strategy of a startup - Dobreva, Maria Lubomirova (2020)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management